(untitled) (Dhaka University Journal of Biological Sciences, 2024)
In recent years, a number of new and undescribed anuran species are being discovered at a very fast rate in South and Southeast Asia. With the revelation of more and more species that were previously considered to be some other species, accurate identification of these morphologically cryptic anurans based on morphology alone have become difficult. In this study, we attempted specieslevel identification of 15 frog specimens belonging to the families Dicroglossidae and Microhylidae of Bangladesh by analyzing their 16S and 12S rRNA gene sequences. The collected specimens were successfully identified to be belonging to eight different species, namely Fejervarya dhaka, F. asmati, F. pierri and F. orissaensis; Euphlyctis kalasgramensis and Euphlyctis sp.; Microhyla berdmorei and M. mymensinghensis using BLAST and maximum likelihood analyses. In some cases the frog samples showed morphological resemblance but after molecular analysis they were found to be different and in another case morphologically distant samples were found to be molecularly similar. For example, two of the specimens (ESP 01, ESP 02) turned out to be E. kalasgramensis at molecular analysis, however, did not match with the morphological and morphometric descriptions (specially snout-vent length) described previously. Moreover, a species is suspected to be still undescribed and another species namely M. berdmorei was thought to be absent in Bangladesh which has been recorded in our study. Thus, morphological ambiguity strengthens the urge for molecular analysis for proper identification. Dhaka Univ. J. Biol. Sci. 33(2): 27-52, 2024 (July)